Penggunaan Media Permainan Ular Tangga dalam Meningkatkan Hasil Belajar Anak pada Materi Bilangan Loncat kelas A RA Ibnu Umah - Irma Muti; Neng Awalia Farida; Hartanti Pungkas Baya (Jurnal El-Audi, 2024)
Skipping numbers are a fundamental concept in mathematics that is important to introduce from an early age because they are directly related to logical thinking, arithmetic, and number patterns. A problem faced in mathematics learning in early childhood education (PAUD), particularly in the topic of jumping numbers, is the low learning outcomes of students. This study aims to determine the improvement in student learning outcomes through the use of the snakes and ladders game on the topic of jumping numbers. The background of this study is the low interest and learning outcomes of students in mathematics learning, particularly in understanding the concept of jumping numbers. The research method used was Classroom Action Research (CAR), implemented in two cycles. The subjects were group B students at an early childhood education institution, with a total of 30 participants. Data were collected through observation, learning achievement tests, and documentation. The results showed a significant improvement in student learning outcomes after the implementation of the snakes and ladders game. In the first cycle, student learning completion only reached 62%, while in the second cycle, this increased to 93%. This improvement demonstrates that the Snakes and Ladders game can create a fun learning environment, increase student active engagement, and facilitate understanding of the concept of jumping numbers. Therefore, it can be concluded that the use of the Snakes and Ladders game is effective in improving student learning outcomes in the topic of jumping numbers in Early Childhood Education (PAUD).